The impact of marketing consultancy on small/medium sized firms - Farhangmehr, Minoo (2021)
This study looks at a programme designed to influence the practice of marketing planning in small/medium sized firms and analyses the impact of marketing planning on the firms when they are provided with such a plan. The study confirms that the incidence of marketing planning in small firms is very low. The results suggest that an evaluation of the programme based only on producing a plan and then implementing it, is inadequate. The real effect of the exercise is also its impact on knowledgeability within firms. Involvement of firms in the marketing planning process increases awareness and knowledgeability of marketing planning. It is argued that the effect will result in the gradual adoption of formal marketing planning by firms. Not only does the experience increase knowledgeability, but the results also indicate that the value of marketing planning to a firm is related to knowledgeability. Firms regard the exercise as valuable if it has had a positive impact on their understanding of marketing and strategic issues. More importantly, increased knowledgeability encourages firms to implement more of the recommendations contained in a plan, which can lead to better performance. The results also indicate that the marketing consultant can have an important role in fostering strategic orientation and marketing awareness in managers of small/medium sized firms. The effectiveness of the programme depends greatly on both the performance of the consultant who prepares the plan and the way the scheme operates.